Performance comparison between fixed panel, single-axis and dual-axis sun tracking solar panel system - Chowdhury, Kamrul Islam; Alam, Md.Iftekhar-ul; Bakshi, Promit Shams (BRAC University, 2018)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2017.